Corporate social responsibility dan kesejahteraan masyarakat: pendekatan triple bottom line - Arif Widyatama; Andi Sabirin; Sulastia Ningrum (Universitas Medan Area, 2021)
The purpose of this study is to understand in depth the implementation of Corporate social responsibility (CSR) in improving the welfare of the community through the CSR program conducted by PT. PLN Region Sulutenggo. The research method used is interpretive, namely understanding from various informants' perspectives regarding the implementation of CSR. The results of this study indicate that the implementation of PT PLN Sulutenggo Region has carried out various work programs that were born through social mapping obtained by phenomena or problems of residents in the area where PT PLN operates, including in the fields of education and health. Therefore, PT PLN must actively participate in continuing to be committed to its work programs. This research has implications for the implementation of the triple bottom line which is fundamental to the implementation of CSR, because companies are not only required to increase revenue but also contribute to two other aspects, namely social and environmental so that the work program of the company's CSR can prosper the community around PT PLN Sulutenggo Region.